Hedonic regression for digital cameras in Germany - Peter Winker; Franziska Rippin (Universität Erfurt, Staatswissenschaftliche Fakultät, 2005)
Standard measures of consumer price inflation are based on a bundle of representative goods. It is well known that this approach might overstate inflation for new products and products with fast increasing quality. For this reason, hedonic adjustment methods have been proposed and introduced in official statistics for some products like personal computers. In this contribution, we consider the application of a hedonic regression to digital cameras, which have been introduced in the product bundle of the German consumer price index in 2003 - so far without hedonic quality adjustment. We present first results on hedonic price measurement for digital cameras in Germany for the time period 1999 to 2004. The results are based on data sampled from public interest journals and advertisements.
Keywords: 330; Hedonic regression; hedonic price index; quality adjustment; Hedonischer Preis; Regression; Fotoapparat; Lebenshaltungsindex; Schätzung; Theorie; Deutschland